Beneficiation Experiment of a Carbonate Fluorite Ore in Guizhou - Jian Huang; Wei Peng; Wubin Li; Zhenjie Wang; Anrong Liu (Kuangchan zonghe liyong)
This is an essay in the field of mineral processing engineering. There is a 40.56% CaF2 in a Carbonate fluorite ore in Guizhou. The ore composition is complex and the content of carbonate gangue minerals is high. The flotation experiment was carried out with a new collector LY-14 developed by ourselves. Using the closed-circuit test process of "one coarse, six fine and one sweep", under the conditions of grinding fineness of -0.074 mm, content of 81.42%, dosage of Na2CO3 of 1 200 g/t, dosage of acidified sodium silicate of 1 200 g/t, dosage of tannin of 100 g/t and dosage of collector LY-14 of 600 g/t, fluorite concentrate with CaF2 grade of 96.35% and CaF2 recovery of 91.47% was obtained.